Moving beyond disease-focused decision making: understanding competing risks to personalize lung cancer treatment for older adults - Taylor, Lauren J.; Maloney, James D. (Journal of Thoracic Disease; Vol 9, No 1 (January 24, 2017): Journal of Thoracic Disease, 2017)
Every year in the United States alone over 500,000 adults age 65 years and older undergo high-risk surgery. For many of these procedures, including lung resection, annual volume is increasing (1).